Profiles of Cortical Visual Impairment (CVI) Patients Visiting Pediatric Outpatient Department - Parajuli, Rojeeta; Adhikari, Srijana; Shrestha, Ujjowala (Nepalese Journal of Ophthalmology, 2020)
Introduction: Cortical visual impairment denotes vision loss from pathology posterior to the lateral geniculate nucleus. The pathology may involve the optic radiations, as well as the occipital cortex.Objective: To find out the profiles of cortical visual impairment patients visiting the pediatric outpatient department.Materials and Methods: The study is a hospital based retrospective study in which all consecutive patients diagnosed with cortical visual impairment were included. A total of 40 patients were collected. Detailed history taking and clinical examination was done. Visual acuity was taken by fixation and follows method. Among 40 patients, only two patients were advised to use glass and the rest did not have significant refractive error. Myopia ranged from (-2D to -5D) and five patients were myopic. Astigmatism ranged from (-0.5 to -2.5 x 108°) and 10 patients had astigmatism. Suspected patients were advised for Computed Tomography/ Magnetic Resolution Imaging (CT/MRI) of the brain.Results: The male: female ratio was 3:2, the age group ranged from 4 months to 8 years old, antenatal checkup history was uneventful in 77.5% cases, history of birth asphyxia was present in 87.5% cases, postnatal checkup history was eventful in 67.5%, associated systemic illness was present in 60%, anterior segment examination was normal in 92.5%, posterior segment examination was normal in 72.5%, CT/MRI findings were abnormal in 57.5% and was not done in 30% of cases. Antenatal history was described as uneventful if there was absence of diabetes mellitus, hypertension, fever and intake of any medicine. Postnatal history was described as uneventful if there was absence of febrile convulsion, meningitis, encephalocele, encephalopathy, epilepsy or hydrocephalus.Conclusion: Birth asphyxia and postnatal infections are the major causes for cortical visual impairment. We can mitigate cortical visual impairment by limiting birth asphyxia and postnatal infections.